Chromosomal variability and morphological notes in Graomys griseoflavus (Rodentia, cricetidae, sigmodontinae), from Catamarca and Mendoza provinces, Argentina - Lanzone, Cecilia (2014)
Genetic variability in rodents is extremely wide and a fruitful field of research. Graomys griseoflavus is a phyllotine rodent, endemic to South America, polymorphic for Rb rearrangements. However, few individuals and populations were studied cytogenetically to date, considering its wide distribution. We present and compare chromosomal data from Mendoza and Catamarca provinces, contrasting previous hypothesis about its karyotypic evolution. All populations were polymorphic for Rb rearrangements; in addition, we describe a new fusion from Mendoza. The presence of more than one heterozygous fusion in several localities refute the hypothesis proposed for this species that for a new fusion to be generated the others must occur in homozygosis. The recorded 2n have an irregular geographic distribution. The extra short arms detected are additional factors of chromosome variability. Some external qualitative characters (i.e., coloration) show certain variability. In some quantitative external and cranial characters, a low degree of sexual dimorphism was detected. However, there were not significant differences in external and cranial metrics variables among localities indicating low degree of differentiation, as reported in previous works; neither the coefficients of variation of these variables had high values compared to other related species. While a larger sample is needed for these different types of characters, the high chromosomal variability does not seem to correspond with comparable degrees of morphological and mitochondrial variability in G. griseoflavus.